1985
DOI: 10.1111/j.1440-169x.1985.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Inductive Capacities for the Dorsal Mesoderm of the Dorsal Marginal Zone and Pharyngeal Endoderm in the Very Early Gastrula of the Newt, and Presumptive Pharyngeal Endoderm as an Initiator of the Organization Center*

Abstract: The organization center of Cynopspyrrhogaster was divided into Parts 1, 2 and 3 of equal size (0.3 x 0.4 mm2) with presumptive fates as pharyngeal, pharyngeal+prechordal +trunk notochord, and trunk-tail notochord, respectively. Movements and changes in size and shape of each part were followed through gastrulation. Differentiation tendencies of each part were examined under three conditions: I, isolated; 11, sandwiched with presumptive ectoderm; 111, sandwiched with presumptive ectoderm after preculture in iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…More recently, Kaneda and Hama [23] have shown that the trunk organizer does not acquire its final inducing ability until after involution during gastrulation. The presumptive head organizer before gastrulation behaves as an inducer of trunk structures and again only acquires its head-inducing characteristics gradually during gastrulation [24]. Taken together these reports suggest that definitive A-P axial properties in dorsal mesoderm are not determined until at least mid-gastrula stages.…”
Section: Classical Embryological Experimentssupporting
confidence: 51%
“…More recently, Kaneda and Hama [23] have shown that the trunk organizer does not acquire its final inducing ability until after involution during gastrulation. The presumptive head organizer before gastrulation behaves as an inducer of trunk structures and again only acquires its head-inducing characteristics gradually during gastrulation [24]. Taken together these reports suggest that definitive A-P axial properties in dorsal mesoderm are not determined until at least mid-gastrula stages.…”
Section: Classical Embryological Experimentssupporting
confidence: 51%
“…In addition, Cynops activin-treated ectoderm induces a whole secondary axis (from head to tail) when transplanted into the VMZ of blastulae . These phenomena were also seen in Cynops presumptive endoderm of the DMZ next to axial mesoderm (Hama et al 1985;Yamamoto & Suzuki 1994;Ninomiya et al 1998). These reports suggest that activin-treated ectoderm is equivalent to endoderm of the DMZ and acts as an organizer in Cynops.…”
Section: Introductionmentioning
confidence: 73%
“…The same region induces the formation of heads when it is precultured in saline for a specific period. 35 These results suggest that the age of the organizer influences the formation of the anteroposterior body pattern.…”
Section: In Vitro Control Of Fundamental Embryonic Form By Activinmentioning
confidence: 91%